Habitat use and diet selection of reintroduced white rhinoceros (Ceratotherium simum) in Pafuri, Kruger National Park - Pedersen, Gayle (Stellenbosch : Stellenbosch University, 2009)
Thesis (MSc (Conservation Ecology and Entomology))--Stellenbosch University, 2009.